2022
DOI: 10.53730/ijhs.v6ns3.5913
|View full text |Cite
|
Sign up to set email alerts
|

Papillon-Lefevre syndrome with arachnodactyly and associated aggressive periodontitis

Abstract: Papillon-Lefevre Syndrome (PLS) is a autosomal recessive genetic disorder. The prevalence of this disorder has been reported to be 1 to 4 per million in the general population. The prime features of PLS include palmar-plantar hyperkeratosis along with premature loss of deciduous and permanent teeth due to aggressive periodontitis. Radiological feature involves severe destruction of alveolar bone giving teeth a typical “floating in air” appearance along with intra-cranial calcifications. Clinical findings of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Periodontal inflammation plays a dominant role in clinical diagnosis( Henderson et al, 2009 ). Because the periodontium is involved, the dentist is typically the first to diagnose the PLS( Tariq et al, 2022 ). One prior study showed that patients with PLS exhibit similar bacterial flora, including spirochetes, and populations of Epstein–Barr virus and cytomegaloviruses, as in individuals with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal inflammation plays a dominant role in clinical diagnosis( Henderson et al, 2009 ). Because the periodontium is involved, the dentist is typically the first to diagnose the PLS( Tariq et al, 2022 ). One prior study showed that patients with PLS exhibit similar bacterial flora, including spirochetes, and populations of Epstein–Barr virus and cytomegaloviruses, as in individuals with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…One prior study recommended antibiotics such as amoxicillin or amoxicillin with clavulanic acid. The suggested dosage was 20–50 mg/kg/day or 20–40 mg/kg/day, respectively, administered in divided doses every 8 h. It is advised to administer antibiotics for a duration of two weeks following tooth extraction to prevent postoperative complications( Tariq et al, 2022 ). In the book, Pediatric Dentistry Infancy through Adolescence, successful treatment outcomes in children were also documented through the implementation of antibiotic therapy( Casamassimo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation